Feasibility test application of information systems in the media as a learning in vocational school - Jumiyanto Widodo; Sutaryadi Sutaryadi; Chairul Huda Atma Dirgatama; Arif Wahyu Wirawan (Intelektual Pustaka Media Utama, 2020)
This study aims to determine the level of eligibility of the application of staffing information systems as a learning media for automation of staffing governance in the Vocational. This research method uses quantitative research methods. Data collection techniques are done using a questionnaire and analysis of needs using quantitative data analysis. Based on the results of the feasibility test on the application of the staffing information system as a learning media for automation of the governance of staffing above it was concluded that the application of the staffing information system can be categorized as very suitable for use in the learning process in the Vocational School in the Field of Automation and Office Management. Based on the results of the assessment of material experts, validation of media experts, expert practitioners and materials that show the results of the assessment of 89.2% of material experts; 95% assessment of media experts; 90% of expert practitioners, so the application is very feasible to use in the learning process.